2017
DOI: 10.1111/iji.12338
|View full text |Cite
|
Sign up to set email alerts
|

The association between MICA/MICB polymorphism and respiratory syncytial virus infection in children

Abstract: MICA/MICB gene polymorphisms are related to several cancers and infectious diseases, but there are no reports on the association between MICA/MICB gene polymorphisms and respiratory syncytial virus (RSV) infection. To clarify the association between MICA/MICB gene polymorphisms and infection of RSV in children, we collected fresh blood samples from paediatric patients with and without pneumonia after RSV infection. The MICA/MICB alleles were characterized by PCR sequence-specific primers (PCR-SSP) and PCR sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This system can be utilized to study the function of various known ligands. MICA, a ligand of NKG2D, is a stress induced protein expressed in epithelium, fibroblasts, keratinocytes, endothelial cells, and monocytes and involved in innate and adaptive immune response such as autoimmune diseases , infection , transplant rejection . There are two dozen MICA and MICB variants distributing in different populations with unclear differences in functions.…”
Section: Discussionmentioning
confidence: 99%
“…This system can be utilized to study the function of various known ligands. MICA, a ligand of NKG2D, is a stress induced protein expressed in epithelium, fibroblasts, keratinocytes, endothelial cells, and monocytes and involved in innate and adaptive immune response such as autoimmune diseases , infection , transplant rejection . There are two dozen MICA and MICB variants distributing in different populations with unclear differences in functions.…”
Section: Discussionmentioning
confidence: 99%
“…118 Furthermore, allele MICA*002:01/A9 and haplotype MICA*002:01-MICB*005:02 were negatively associated with RSV respiratory tract infections in another study. 119 (potassium voltage-gated channel subfamily D member 3). 121 Recently, another GWAS study showed that NKG2D gene variation (rs10772271) may predispose infants to bronchiolitis.…”
Section: Janssen Et Al Through Testing 384 Snps In 220 Candidate Genementioning
confidence: 99%
“…By evaluating polymorphisms within ICAM‐1 , VCAM‐1 , and E‐selectin genes, Krueger et al found no evidence for association of any polymorphism with severe RSV infections . Furthermore, allele MICA *002:01/A9 and haplotype MICA *002:01‐MICB*005:02 were negatively associated with RSV respiratory tract infections in another study . High et al found that human MARCO (an innate immunity scavenger receptor) promoter SNP (rs1318645) that caused loss of gene expression, increased in vitro cellular response to RSV infection, and associated with increased risk of disease severity in children infected with RSV .…”
Section: Introductionmentioning
confidence: 99%
“…MICA/B were the rst identi ed ligands for NKG2D whose genes have been mapped to the MHC class I region, in the proximity of HLA-B locus [13]. These highly glycosylated proteins are present in membranebound and soluble isoforms and bear complete polymorphism with more than 100 alleles [13,16,17]. [18].…”
Section: Introductionmentioning
confidence: 99%